Pastoralists and farmers conflict: rights or greediness - Aluko, Opeyemi Idowu (Journal of the Belarusian State University. International Relations, 2021)
Pastoralists are basically migrants who do not have a permanent abode but migrates from one graze land to the other. The migration may be across international borders. Farmers on the other hand have a quasi-permanent abode. However the farmland crops are so precious to the farmers while getting grasses including crops on the farmland just for the cattle to survive is the priority of the pastoralists. This conflict of interests between the pastoralists and the farmers is a major crisis goalpost in West Africa among other violence such as ethno-religious violence. The focus of this paper is to examine the extent of damages caused due to claims of right or greediness by the pastoralists and the farmers in the society. The relative deprivation theoretical framework is used to examine the question of the place of mutual respect, peaceful co-existence and good neighbourliness. The paper concludes on the premise of respecting boundaries between the graze and the farmland and the use of modern husbandry ranching instead of a nebulous nomadic system.
Keywords: conflict; land dispute; pastoralism; rule of law; urban violence